The Effect of Ice Breaking on Student Learning Outcomes in Islamic Religious Education Subjects in Elementary Schools - Nurhidayah, Anita; Nawawi, M. Latif; Muamalah, Husnul (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
This study examines the effect of the application of ice breaking techniques on students' learning outcomes in Islamic Religious Education subjects at State Elementary School 2 Bandarsari, Padangratu District, Central Lampung Regency. Against the background of the increasing importance of creating an inclusive and interactive learning environment, the aim of this study is to evaluate the effectiveness of the ice breaking method in improving students' understanding of religious materials. This study used a quantitative approach by involving IV A and IV B students as research samples. Data were collected through tests before and after the application of ice breaking and analyzed using descriptive and inferential statistical analysis. The results showed a significant increase in students' learning outcomes after the application of the ice breaking method, indicating the positive impact of this approach on students' understanding of Islamic Religious Education materials. The implications of the findings highlight the importance of integrating ice breaking methods in religious learning at the primary school level to improve students' engagement and their overall learning outcomes. This research provides a basis for teachers and educational policy makers to consider the use of ice breaking methods as an effective learning strategy in the context of religious learning.